A Critical Review of the Sustainability of Multi-Utility Tunnels for Colocation of Subsurface Infrastructure - Bergman, Filip; Anderberg, Stefan; Krook, Joakim; Svensson, Niclas (Frontiers in Sustainable Cities, 2022)
Multi-utility tunnel (MUT) have received increasing attention as an alternative method for installing subsurface infrastructure for the distribution of electricity, telecommunications, water, sewage and district heating. MUTs are described as a potentially more sustainable technology than conventional open-cut excavation (OCE), especially if the entire life cycle of these cable and pipe networks is taken into account. Based on an extensive review of the academic literature, this article aims to identify and critically examine claims made about the pros and cons of using MUT for the placement of subsurface infrastructure. Identified claims are mapped, and their validity and applicability assessed. These claims are then analyzed from a sustainability perspective, based on the three sustainability dimensions and a life cycle perspective. The results show that a variety of advantages and disadvantages of using MUTs for subsurface infrastructure are highlighted by the articles, but several of these are without any empirical support. When some form of empirical support is presented, it usually comes from case-specific analyses of MUTs, and the applicability in other MUT projects is seldom discussed. Economic performance is the sustainability dimension that has received the most attention, while environmental performance has not been analyzed in the reviewed literature, which is a major limitation of the current knowledge. In summary, the knowledge about the sustainability performance of using MUTs for subsurface infrastructure is still limited and incoherent. In order to increase the knowledge, this article points out the importance of new case studies, in which the sustainability consequences of using MUTs for subsurface infrastructure are mapped and evaluated by combining both quantitative and qualitative assessment methods.